Unwanted penile engorgement in pediatric patients under anesthesia: The role of anesthetic technique and other contributing factors - Hasan, Muazzam; Nadeem, Abu; Raza, Nadeem; Ahmed, Syed Moied (Indian Journal of Child Health, 2018)
Background: The mechanism behind intraoperative penile engorgement (PE) is complex. One common myth is that PE occurs more frequently during spinal anesthesia than the general anesthesia. Objective: The objective of this study was to report the incidence and management of intraoperative PE in pediatric patients undergoing urogenital operations under spinal anesthesia with or without sedation over a period of 1 year. Methods: Patients aged between 2 and 12 years, posted for elective urogenital surgery of expected duration <1 h, were given spinal anesthesia with or without supplemental sedation as per child’s cooperation. Incidence of unwanted intraoperative PE, time of onset of the SA, length of surgery, attempts of successful lumbar puncture, need for supplemental systemic sedation, conversion to general anesthesia, and perioperative complications were recorded. Results: A total of 348 patients were included in the study. Only two (0.005%) cases developed PE intraoperatively. 225 (64.6%) children required systemic sedation along with spinal blockade. 123 (35.3%) cases were successfully operated under spinal alone without any sedation. None of the cases required conversion into general anesthesia. The mean time of onset of spinal blockade was 100±54 s. First attempt success rate of lumbar puncture was 83% while 16.9% of patients required the second attempt. There were no major complications in any child in the perioperative period. Conclusion: Spinal anesthesia is associated with very less incidence of PE and can be practiced safely in the pediatric patients. Just the fear of development of PE should not bias the choice of an esthetic technique toward general anesthesia.